PENGARUH PENGGUNAAN LIMBAH PLASTIK POLYPROPYLENE (PP) SEBAGAI CAMPURAN AGREGAT KASAR TERHADAP KUAT TEKAN DAN TARIK PADA BETON FC’ 25 MPA - Angga Pirman Firdaus; Jonbi (Jurnal Infrastruktur, 2017)
Indonesia ranks second in the world's largest plastic waste producer after China. Each year, Indonesia can contributeup to 187.2 million tons of plastic waste, while China reaches 262.9 million tons of plastic waste. Based on the data, one way to utilize plastic waste by using plastic waste as a mixture of concrete, where the plastic used is polypropylene (PP) plastic with different percentage of concrete mixture, the test includes compressive strength test and tensile concrete. The results of concrete compressive strength testing with polypropylene (PP) plastic waste mixture of 5%, 10% and 15% at age 28 in aggregate aggregate mixture decreased by 5.15%, 6.89% and 13.53%. As for the result of concrete tensile strength test with polypropylene (PP) plastic waste mixture of 5%, 10% and 15% at age 28 in crude aggregate mixture decreased 17,61%, 24,13% dan 23,24%.